RELIGIUSITAS SEBAGAI MODAL SOSIAL MAHASISWA E-PRENEUR PRODI SOSIOLOGI AGAMA IAIN KEDIRI - Ika Silviana (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2021)
Technological developments have accelerated the transformation of trade patterns in Indonesia. This cannot be denied because of the incessant wave of the industrial revolution 4.0 that has infiltrated to the smallest line of production. The e-commerce system is able to accommodate most all activities of small, medium and large economic actors. In this context, students have begun to realize the important of entrepreneurial skills. This study focuses on portraying a religiosity aspect of e-preneur has been developed at the Sociology of Religion Study Program at IAIN Kediri. Through the phenomenological approach, data mining was carried out on 4 selected informants using observation, interview and documentation methods. By using James Coleman's theory of social capital and the dimensions of religiosity, the following results are obtained: (1) religiosity aspect of e-preneur student is formed through the formation of education and habituation in the family environment, religion-based formal education and Islamic boarding schools; (2) the religious practices of entrepreneurship are carried out through the application of religious values, reflecting on experiences, and determining life goals after graduation; (3) religiosity is used to build social capital in the form of belief in success by applying believed in religious values. (4) The practice of e-preneur religiosity produces 3 attitudes, which consist of independence, realistic (waqi'iyah), and moderation (washathiyah). Perkembangan teknologi mendorong percepatan transformasi pola perdagangan di Indonesia. Hal ini tidak dapat ditolak karena gencarnya gelombang revolusi teknologi 4.0 yang telah menyusup hingga lini terkecil. Sistem e-commerce dapat mewadahi aktivitas pelaku ekonomi kecil, menegah dan atas. Kesempatan ini mulai dilirik oleh kalangan mahasiswa sebagai upaya mengasah kecakapan berwirausaha. Penelitian ini memfokuskan pada potret religiusitas mahasiswa e-preneur Prodi Sosiologi Agama di IAIN Kediri. Melalui pendekatan fenomenologi dilakukan penggalian data pada 4 subyek terpilih dengan metode observasi, wawancara dan dokumentasi. Dengan menggunakan teori modal sosial James Coleman dan dimensi religiusitas didapatkan hasil sebagai berikut: (1) religusitas mahasiswa e-preneur terbentuk melalui landasan pendidikan dan pembiasaan di lingkungan keluarga, pendikan formal berbasis agama dan pesantren. (2) praktik religiusutas berwirausaha dilakukan melalui penerapan nilai agama, merefleksikan pengalaman, dan menentukan tujuan hidup setelah lulus. (3) Religiusitas digunakan untuk membangun modal sosial berupa kepercayaan akan kesuksesan dengan menerapkan nilai-nilai agama yang diyakini. (4) Praktik religiusitas e-preneur menghasilkan 3 sikap yang mencakup kemandirian, realistis (waqi’iyah), dan moderasi (washathiyah).